Effect of coconut shell powder [CSP] on cure characteristics, physical and mechanical properties of nitrile rubber [NBR] composites / Nurliyana Mohd Sharif - Mohd Sharif, Nurliyana (2020)
Coconut Shell Powder (CSP) was used as reinforcing agent in Nitrile rubber (NBR). Untreated CSP and alkali treated CSP were used as filler materials in the preparation of NBR composites. The influence of filler loading alkali treatment on the cure characteristics, physical and mechanical properties of the composites were analyzed. The characteristics of the untreated and treated CSP were confirmed from FTIR studies through the shifting and broadness of the absorption peak. The NBR composites incorporated with treated CSP (10 phr) achieved the optimum cure time, the highest tensile strength (2.80 MPa) and elongation at break (128.12 %). However, the hardness and the tensile modulus of the NBR composites increasing with the addition of the treated CSP filler loading. The alkali treatment on CSP can be concluded to enhance the curing characterization, physical and mechanical properties of NBR composites.